Oral tradition and the adat constitution of Negeri Sembilan: A study of traditional Malay constitutional government and constitutional monarchy - Haron, Nadzan (2014)
Constitution is the collection of rules which establish and regulate or govern the government. These rules are partly legal and partly non-legal, taking the form of usages, understandings, customs or conventions.Constitutional laws are the fundamental laws that establish and govern the structure, functions and powers of main organs of government and the relation between each organ with the other and with the people. It is the collection of legal rules and non-legal rules which govern the government of a country, (K.C. Wheare, Modern Constitutions. P. 1; S.A. de Smith, Constitutional and administrative law , p.7). Constitutional government is a government that is governed based on a constitution. A government whose authority and construction are defined by a constitution. Constitutional monarchy refers to the monarch or the political system in which the powers and authority of the monarch are restricted to those granted under the constitution and laws of the state; or the traditions and values of the society concerned.It is a form of democratic government in which a monarch acts as nonpolitical head of state within the boundaries of a constitution whether written or unwritten. A sovereign who reigns but does not rule. This form of government differs from absolute monarchy, in which the monarch controls political decision-making and is not effectively bound by a constitutional order.